2017
DOI: 10.1109/tvcg.2016.2598466
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Dimension Coverage to Support Exploratory Analysis

Abstract: Data analysis involves constantly formulating and testing new hypotheses and questions about data. When dealing with a new dataset, especially one with many dimensions, it can be cumbersome for the analyst to clearly remember which aspects of the data have been investigated (i.e., visually examined for patterns, trends, outliers etc.) and which combinations have not. Yet this information is critical to help the analyst formulate new questions that they have not already answered. We observe that for tabular dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Behavior Graphs : Problem‐solving behavior can be modeled as a set of states along with a set of operations for moving between states [New72], including visual analysis [WMA∗16b, STM17, WQM∗17, SvW08, ST15, jJKMG07]. Graphs can capture more complex paths and patterns, such as back‐tracking or state revisitation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior Graphs : Problem‐solving behavior can be modeled as a set of states along with a set of operations for moving between states [New72], including visual analysis [WMA∗16b, STM17, WQM∗17, SvW08, ST15, jJKMG07]. Graphs can capture more complex paths and patterns, such as back‐tracking or state revisitation.…”
Section: Related Workmentioning
confidence: 99%
“…Wongsuphasawat et al define depth and breadth in terms of the total unique states analyzed [WMA∗16b, WQM∗17] (also considered by Sarvghad et al [STM17]). However the interactions that produce these states, and thus the states themselves, are not independent.…”
Section: The Structure Of Analysis Sessionsmentioning
confidence: 99%
“…Coordination and synthesis strategies between asynchronous data analysts were also previously studied [37,40,41], sharing our interest in understanding and consolidating work of previous investigators. Robinson [37] focused on the co-located synthesis of findings after an asynchronous distributed analysis phase.…”
Section: Collaborative Visual Analyticsmentioning
confidence: 99%
“…Robinson [37] focused on the co-located synthesis of findings after an asynchronous distributed analysis phase. Sarvghad et al [40,41] found visualizing data dimension coverage of a previous analyst's exploration can promote awareness and understanding, as well as the question formation process, in tabular data analysis.…”
Section: Collaborative Visual Analyticsmentioning
confidence: 99%
“…In fact, we seem to go faster than we have time to note down" (a participant from study [5]). Moreover, our domain experts were not able to build a clear mental model of past exploration, nor did they have any means to evaluate whether they had a robust or exhaustive exploration strategy [26]. Indeed, the lack of support tools for sensemaking of past exploration is common in many EDA systems [19,10,16].…”
Section: Introductionmentioning
confidence: 99%